2012
DOI: 10.5923/j.ijmc.20120203.06
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Microwave Properties of Graphene Nanoplatelets /Carbon Black Filled Natural Rubber Composites

Abstract: Natural rubber (NR) based nanocomposites containing a constant amount (50 phr) of standard furnace carbon black and graphene nanoplatelets (GNP) in concentrations from 1 to 5 phr have been prepared. Their dielectric (d ielectric permittiv ity, dielectric loss) and microwave propert ies (coefficients of absorption and reflect ion of the electro magnetic waves and electromagnetic interference shielding effectiveness) have been investigated in the 1-12 GHz frequency range. The results achieved allow us to reco mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…All of these factors during deformation contribute to the formation of a network structure containing cross-linked chemical chains, nanofiller, and crystallizable networks in the NR/filler nanocomposite. Dishovsky et al [7] have reported that carbon black filled NR-containing graphene nanoparticles (GNPs) were found to improve the dielectric properties and microwave properties, viz., coefficient of absorption and reflection of the electromagnetic waves and electromagnetic interference shielding effectiveness. Stiffness improvement by thermally reduced graphene oxide (TRG) was found to be more pronounced for elastomers [8], such as NR and styrene butadiene rubber (SBR), due to the higher stiffness between the matrix and the filler.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors during deformation contribute to the formation of a network structure containing cross-linked chemical chains, nanofiller, and crystallizable networks in the NR/filler nanocomposite. Dishovsky et al [7] have reported that carbon black filled NR-containing graphene nanoparticles (GNPs) were found to improve the dielectric properties and microwave properties, viz., coefficient of absorption and reflection of the electromagnetic waves and electromagnetic interference shielding effectiveness. Stiffness improvement by thermally reduced graphene oxide (TRG) was found to be more pronounced for elastomers [8], such as NR and styrene butadiene rubber (SBR), due to the higher stiffness between the matrix and the filler.…”
Section: Introductionmentioning
confidence: 99%
“…First Omar et al [21] have reported microwave studies based on carbon black and graphene filled natural rubber composites and they limited the frequency region up to 12 GHz. They used graphene from Hayzen Engineering Co. Ankara, and the maximum amount incorporated was 10 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] However, to achieve a higher dielectric constant, a large amount of ceramic fillers (the concentration of the ceramic fillers is often over 50 vol.%) needs to be filled into the polymer matrix, which will dramatically increase the dielectric losses and brittleness of the composites. Therefore, polymer/modified conductive fillers (such as carbon black, 14 carbon nanotubes, 15,16 graphene, 17,18, etc.) composites have been identified as a promising approach to achieve the combination of the two outstanding dielectric and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%